Fermentation dynamics of millet beverages: Microbial interactions, nutritional enhancements, and health implications - Tanu Tomar; Angel Sachdeva; Joydeep Dutta; Abdel Rahman Mohammad Al Tawaha; Arun Karnwal; Tabarak Malik; Manickam Selvaraj (Food Chemistry: X)
Fermented millet beverages are gaining attention as a sustainable and nutritious alternative to traditional functional foods, combining the nutritional benefits of millets with the transformative effects of fermentation. This review explores the microbial dynamics, biochemical changes, and health benefits of these beverages. Fermentation boosts nutrient bioavailability, reduces anti-nutritional factors, and produces bioactive compounds like antioxidants and probiotics that support gut health, metabolism, and immunity. It also enhances the synthesis of vitamins, minerals, and peptides, offering potential benefits for managing chronic conditions. Key factors such as temperature, pH, oxygen levels, and substrate composition influence fermentation, with specific microorganisms enhancing both nutritional and sensory qualities. These beverages align with sustainability goals, as millets thrive in resource-limited environments, and their gluten-free nature caters to dietary needs, including those with celiac disease. The review highlights the cultural significance of millet beverages while advocating for their integration into modern health markets and commercial viability